SMALL AND MEDIUM ENTERPRISES (SMES) FACE DIGITAL MARKETING - Aries Kurniawan; Moh Asharudin (Asosiasi Fakultas Ekonomi dan Bisnis Perguruan Tinggi Muhammadiyah, 2018)
The patterns of marketing in business have changed rapidly. While in the past, marketing was done solely through direct face-to-face transaction, the current existence of the internet leads to alternative options for commercial activities, including by using a Smartphone or gadget, customers can have transactions via various applications. These applications also offer a variety of products, including apparels, food, household needs as well as tertiary needs. To keep with the pace, business actors also change their marketing patterns. In addition to advertise and sell the products through conventional method, the internet becomes the marketing media for business actors. Nevertheless, not all of them are able to change their marketing pattern, especially SMEs. The factors of low educational background and lack of knowledge of the internet, development, and technology are the reasons. Considering this condition, it is suggested for business actors to change their marketing pattern according to the developments and technological advances in the community in order to survive.